PONDOK PESANTREN, MADRASAH DAN SEKOLAH : KEBIJAKAN SKB 3 MENTRI TAHUN 1975 - Deby Deby (Al-SAMBASY: Jurnal Kajian Pendidikan, 2024)
Madrasah as one of Islamic education in Indonesia has a long history in this nation. Formally, madrasah is developed as a response toward two important conditions, those are the reformation of Islam in Indonesia and education under supervision of Dutch. The implication of such condition in modern era is the issue of the decree of three ministers that reduce the problem dualism in education and theimprovement of the quality of madrasah. The issue of such decree is a stepping point to integrate madrasah to the national system of education.